High-Tech and Nature-Made Nanocomposites and Their Applications in the Field of Sensors and Biosensors for Gas Detection - Daniele Zappi; Matiss Martins Ramma; Viviana Scognamiglio; Amina Antonacci; Gabriele Varani; Maria Teresa Giardi (Biosensors, 2020)
Gas sensors have been object of increasing attention by the scientific community in recent years. For the development of the sensing element, two major trends seem to have appeared. On one hand, the possibility of creating complex structures at the nanoscale level has given rise to ever more sensitive sensors based on metal oxides and metal–polymer combinations. On the other hand, gas biosensors have started to be developed, thanks to their intrinsic ability to be selective for the target analyte. In this review, we analyze the recent progress in both areas and underline their strength, current problems, and future perspectives.